2014
DOI: 10.1177/0883911514528410
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric prodrugs of ampicillin as antibacterial coatings

Abstract: A novel ampicillin prodrug containing two carboxylic acid functionalities was synthesized by reacting ampicillin with acyl chloride in the presence of base. This prodrug was subsequently converted into a poly(anhydride-amide) via solution polymerization. The polymer, which chemically incorporates the ampicillin prodrug into the polymeric backbone, was developed as a film to prevent infections associated with medical devices by controlled, localized release of antimicrobials. The robust polymer coatings exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…83,84 Ampicillin, a commonly used betalactam antibiotic, was chemically incorporated into a poly-(anhydride-amide) backbone using a method similar to that described in section 3.1 (Scheme 6). 85 Bearing a primary amine and a carboxylic acid moiety, ampicillin (23) was reacted with a diacyl chloride (e.g., sebacoyl chloride, 24) to afford the diacid (25). Solution polymerization with triphosgene as a coupling agent resulted in the poly(anhydride- amide) (26).…”
Section: Antibioticsmentioning
confidence: 99%
“…83,84 Ampicillin, a commonly used betalactam antibiotic, was chemically incorporated into a poly-(anhydride-amide) backbone using a method similar to that described in section 3.1 (Scheme 6). 85 Bearing a primary amine and a carboxylic acid moiety, ampicillin (23) was reacted with a diacyl chloride (e.g., sebacoyl chloride, 24) to afford the diacid (25). Solution polymerization with triphosgene as a coupling agent resulted in the poly(anhydride- amide) (26).…”
Section: Antibioticsmentioning
confidence: 99%
“…This approach would confer properties such as high drug loading, enhanced processability and better controlled release kinetics to the polymer . Poly­(anhydride-ester) based polyactives can also be employed as prodrug platforms for the controlled release of various therapeutics and bioactive small organic molecules including antioxidants, anti-inflammatory drugs, , antiseptics, , antibiotics, and antimicrobial drugs . Recently, Madras et al also reported several poly­(anhydride-esters) that contained bioactive molecules such as salicylic acid and aspirin in the polymer main chain. They studied the release kinetics associated with the hydrolytic degradation of the polymer matrix and subsequently investigated their anti-inflammatory and antibacterial activities.…”
Section: Applicationsmentioning
confidence: 99%
“…Poly(actives), or polymeric pro-drugs that rely on degradable linkages for the release of therapeutic agents, can improve chemical stability, enable tunable release profiles, and reduce volatility [15]. Multiple linear poly(actives) have been reported including poly(esters) [16, 17], poly(anhydride-esters) [1825], poly(anhydride-amides) [26], poly(carbonate-amides) [27], poly(carbonate esters) [28], poly(ketals) [29], and poly(oxalate-acetals) [30]. While linear poly(actives) successfully entrap drugs and allow for tunable release profiles, crosslinked poly(actives) represent a relatively unexplored class of degradable drug-releasing materials where opportunities for greater control over degradation profiles, thermomechanical properties, and sample geometry (particles, thin films, or coatings) are available.…”
Section: Introductionmentioning
confidence: 99%